2019
DOI: 10.1038/s42003-019-0369-7
|View full text |Cite
|
Sign up to set email alerts
|

The combination of neoantigen quality and T lymphocyte infiltrates identifies glioblastomas with the longest survival

Abstract: Glioblastoma (GBM) is resistant to multimodality therapeutic approaches. A high burden of tumor-specific mutant peptides (neoantigens) correlates with better survival and response to immunotherapies in selected solid tumors but how neoantigens impact clinical outcome in GBM remains unclear. Here, we exploit the similarity between tumor neoantigens and infectious disease-derived immune epitopes and apply a neoantigen fitness model for identifying high-quality neoantigens in a human pan-glioma dataset. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 72 publications
(95 reference statements)
4
66
0
1
Order By: Relevance
“…Overall our study indicates that while tumor fitness scores can be used to predict response to checkpoint inhibitors, these measures do not seem to predict survival in patients not treated with checkpoint inhibitors where endogenous immune activation is a significant survival factor. It is important to note that while this tumor fitness measure and its underlying assumptions have been adapted with positive predictive results in other contexts (24,25), we find that the exact form of the model is not predictive in these endogenous cases. Nevertheless, it is encouraging to observe that CYT measures are powerful in both treated and untreated patients, which may point to the existence of universally predictive and prognostic immune activation signatures.…”
Section: Discussionmentioning
confidence: 85%
“…Overall our study indicates that while tumor fitness scores can be used to predict response to checkpoint inhibitors, these measures do not seem to predict survival in patients not treated with checkpoint inhibitors where endogenous immune activation is a significant survival factor. It is important to note that while this tumor fitness measure and its underlying assumptions have been adapted with positive predictive results in other contexts (24,25), we find that the exact form of the model is not predictive in these endogenous cases. Nevertheless, it is encouraging to observe that CYT measures are powerful in both treated and untreated patients, which may point to the existence of universally predictive and prognostic immune activation signatures.…”
Section: Discussionmentioning
confidence: 85%
“…Recent trials have shown that endogenous T cells play a significant role in the prolonged survival time of glioma patients (Brown et al, 2016; Zhang et al, 2019). However, glioblastoma-induced immune suppression is a major obstacle to an effective and durable immune-mediated antitumor response.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between malignant cells and their microenvironment is critical for both normal tissue homeostasis and tumor growth, as the immune system can eliminate cancer cells that present neoantigens recognized by receptors of the adaptive immune system or express ligands for activating receptors on innate immune cells (Schreiber et al, 2011). The composition of the various cell types making up the microenvironment can significantly affect the way in which the immune system activates cancer rejection mechanisms (Bedognetti et al, 2016; Joyce and Fearon, 2015; Zhang et al, 2019) and influences the response to immune therapies (Ceccarelli et al, 2016; Cristescu et al, 2018). Therefore, the elucidation of the tumor-host interaction mechanisms plays a crucial role in the understanding of the tumor growth and evolution (Angelova et al, 2018; Bedognetti et al, 2019) and for the identification immuno-oncology therapeutic targets (Hoos, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations